Experiences of mathematics student teachers in a series of science experiments - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2007)
There is an increased interest in finding connections with mathematics and areas outside mathematics such as hard and soft sciences. This increased interest reflected in many of curriculum reforms that took place during the past few decades including the one in Turkish elementary and secondary mathematics education. Hence we believe that Turkish mathematics teachers should have the skills necessary for coping with the changing requirements of the 'new high school' mathematics'. Since research skills is an important requirement, the aim of the paper was chosen to be to investigate 32 mathematics student teachers' reactions during a series of physics experiment, which involves identification of the variables, measurement process and data analysis. In this case study, multi method approach is used in the study to get rich data for answering research questions. The main data collection tools are physics experiment lab reports. A categorization procedure was used to transform the mainly qualitative data into a statistically analyzable form. Findings indicate that student teachers' overall performances on the experiments were not satisfactory. Transforming formal mathematical knowledge into a physics experiment context was problematic. Main conclusion of the study is that teacher training curriculum currently used should be designed to equip the teachers the skills they need to cope with the changing requirements.
Keywords: mathematics education; teacher training; physics experiments